Crystallization behavior of polypropylene/silver nanocomposites using polyethylene glycol as reducing agent and interface modifier. (May 2017) - Camacho, Pablo H; Morales-Cepeda, Ana B; Salas-Papayanopolos, Homero; Bautista, Jesús E; Castro, Carlos; Lozano, Tomas; Sanchez-Valdes, Saúl; Lafleur, Pierre G
In this work, isotactic polypropylene (iPP) nanocomposites were prepared containing silver nanoparticles (Ag-NPs) with a novel and easy method, using polyethylene glycol (PEG) as reducing agent and surface modifier. Ag-NPs were prepared using different amounts in weight of silver nitrate into PEG to induce the formation of Ag-NPs. PP/Ag nano compounds were prepared by melt blend method: single-screw extruder and internal Brabender mixer. The effects of Ag-NPs and PEG on the crystallization, morphology, thermal, and mechanical properties were evaluated. Ag-NPs with a particle size of 80 nm and typical growth of the β-form in iPP were observed. The presence of PEG in samples of PP/Ag-NPs was detected by infrared spectrometry and the peak characteristic of Ag-NPs by ultraviolet–visible analysis. X-Ray diffraction patterns and differential scanning calorimetry thermograms showed the β-phase formation in both of the dispersion methods, but Brabender mixer showed higher percentages of crystallinity (31% of β-phase). The elongation at break was increased and it was directly dependent on the relative amount of crystalline β-phase. PEG is an excellent precursor to get Ag-NPs and a good interface modifier of iPP.